IJCM_203A: Referral Audit of the Public Healthcare system in Bhopal district of Madhya Pradesh - Yadav Sushma (Wolters Kluwer Medknow Publications, 2024)
Background: Referral of patients from doctor to doctor has been identified as high-risk area as patient valuable information can be lost or not quantified properly during the transit. Improving the quality of the referral process and its documentation is important to facilitate timely access to specialty care. Objective: To conduct referral audit of the public health care system in Bhopal district of Madhya Pradesh. Methodology: Audit (document review) or the secondary data pertaining to the out referrals entered in the referral registers was captured after due permission from the administrators/ in- charges of the health facilities using the format for data extraction for referral given by the WHO Referral Register Standards. Quota sample of 50 referred patient entries was taken from the primary and secondary health facilities (1 district hospital, 1 CHC, 2 PHCs) based on patient load and level of care provided in the hospital was taken from OPDs, IPDs and Emergencies wherever out referral registers were maintained. Results: There was a physical presence of out referral register or records in all the health facilities. Details like reason for referral was mentioned in most of the facilities whereas back referral was not mentioned in most of the facilities. Conclusion: Maintenance of the patient health records in the out- referral registers were not up to the required standards stated by the WHO. There is a need for the uniform implementation of state referral policy to ensure quality control of referral mechanisms and maintain continuum of care for better patient outcomes.